Alzheimer’s disease causation by copper toxicity and treatment with zinc - Brewer, George J. (Frontiers in Aging Neuroscience, 2014)
Evidence will be presented that the Alzheimer’s disease (AD) epidemic is new, the disease being very rare in the 1900s. The incidence is increasing rapidly, but only in developed countries. We postulate that the new emerging environmental factor partially causal of the AD epidemic is ingestion of inorganic copper from drinking water and taking supplement pills, along with a high fat diet. Inorganic copper can be partially directly absorbed and elevate the serum free copper pool. The Squitti group has shown that serum free copper is elevated in AD, correlates with cognition, and predicts cognition loss. Thus, our inorganic copper hypothesis fits well with the Squitti group data. We have also shown that AD patients are zinc deficient compared to age-matched controls. Because zinc is a neuronal protective factor, we postulate that zinc deficiency may also be partially causative of AD. We carried out a small 6 month double blind study of a new zinc formulation and found that in patients age 70 and over, it protected against cognition loss. Zinc therapy also significantly reduced serum free copper in AD patients, so efficacy may come from restoring normal zinc levels, or from lowering serum free copper, or from both.